14a+(-93)=49+(-57a)

Simple and best practice solution for 14a+(-93)=49+(-57a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14a+(-93)=49+(-57a) equation:


Simplifying
14a + (-93) = 49 + (-57a)
14a + -93 = 49 + (-57a)

Reorder the terms:
-93 + 14a = 49 + (-57a)

Solving
-93 + 14a = 49 + (-57a)

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '(57a)' to each side of the equation.
-93 + 14a + (57a) = 49 + (-57a) + (57a)

Combine like terms: 14a + (57a) = 71a
-93 + 71a = 49 + (-57a) + (57a)

Combine like terms: (-57a) + (57a) = 0
-93 + 71a = 49 + 0
-93 + 71a = 49

Add '93' to each side of the equation.
-93 + 93 + 71a = 49 + 93

Combine like terms: -93 + 93 = 0
0 + 71a = 49 + 93
71a = 49 + 93

Combine like terms: 49 + 93 = 142
71a = 142

Divide each side by '71'.
a = 2

Simplifying
a = 2

See similar equations:

| 9x+12=192 | | 10-5x=-14+(4-x) | | 5*8x= | | -8=-2-x/2 | | 8x-3=141 | | -16x-(-18)= | | 7x-12x+7= | | 7x+43=386 | | x-5+9x=2x-6+5 | | 11m+5n-2m+9n= | | 6x-31=77 | | 7x-7=12-(5x+7) | | 84=5m+3(4m-6) | | 3x+8=11+2x | | 314=13(x-2)-(12x-13)+2(150+x) | | 8t-2=16(t-2.5) | | 2+2y=-6 | | 4x+3=12x-13 | | 1+3x=16-2r | | 6+9x=8x-12 | | 12h=10h | | 3-4x=44 | | 56x+2=42x+5 | | 5-8x=24 | | 4x-25=105 | | 5x-9=13x-(8x-4) | | 2x-4-5x+10=40 | | 3x+17=59 | | 4(2m+1)=3(2m-5) | | 40x+40=15x+30 | | 3x(2x-1)(x^2-9)(x^2+8)=0 | | 5x^2=3y |

Equations solver categories